The association between embrasure morphology and central papilla recession - Li-Ching Chang (Blackwell Synergy, 2007)
Objective: To discover the association between embrasure morphology and central papilla recession. Material and Methods: The central papilla was visually assessed in 330 adults using standardized periapical radiographs of the maxillary central incisors. The following vertical distances were measured: papilla recession [i.e., the distance from the papilla tip (PT) to the contact point (CP)], bone crest (BC) to contact point (BC–CP), proximal cementoenamel junction (pCEJ) to contact point (pCEJ–CP), and papilla height (PH). The horizontal distance measured was the inter-dental width. Subjects were divided into four groups according to inter-dental width and pCEJ-CP distance, respectively: narrow-long, narrow-short, wide-long, and wide-short. Results: A statistically positive relationship was evident between central papilla recession and age, and a statistically negative relationship was evident between age and PH in all study groups. Conclusions: Central papilla recession as a result of ageing is most frequently associated with a wide inter-dental width and long pCEJ–CP distance. However, other factors affect the likelihood of the presence of the inter-dental papilla, and further study of the interaction among these factors is warranted.